Proceso atención de enfermería en paciente de 36 años de edad con pancreatitis aguda. - Romero Cepeda, Tania Vanessa (2022)
Acute pancreatitis is a sudden inflammation of the pancreas caused by the activation within it of the enzymes it produces for digestion. In severe cases, part of the pancreas is destroyed in a process called necrosis, which produces a generalized inflammatory reaction that can affect other vital organs, among the two most frequent causes (80%) are stones in the gallbladder ( cholelithiasis) and excessive alcohol consumption. Gallstones cause pancreatitis by moving into the bile duct and blocking the outlet of the pancreas into the intestine. Alcohol has a direct toxic effect and can also cause chronic pancreatitis. Other rarer causes are certain medications, a significant increase in blood fat levels (hypertriglyceridemia), a sustained increase in blood calcium (hypercalcemia), obstructions of the pancreatic duct outlet, blows to the abdomen, some surgeries, and performing a test called endoscopic retrograde cholangiopancreatography (ERCP). In approximately 20% of patients the cause is not discovered (idiopathic acute pancreatitis), of which only a small percentage (5%) suffer from new episodes of pancreatitis. It almost always manifests as continuous and intense abdominal pain, localized mainly in its upper part, although it can occupy the entire belly, often radiating to the back "in a belt" and accompanied in most cases by nausea and vomiting. Mainly by analyzing pancreatic enzymes in the blood (amylase or lipase), which are almost always elevated in acute pancreatitis. Other processes can cause abdominal pain and increased pancreatic enzymes, and there are acute pancreatitis with normal levels of pancreatic enzymes, so in some cases it may be necessary to perform a computerized axial tomography (CAT or CT) of the abdomen, if there is any doubt.